Fat-burning exercise strategies to burn fat - Williford, Hank; American College for Sports Medicine; Monterey Bay Video Production Co.; Insight Media ([Indianapolis, In.] : Monterey Bay Video Production Co. [production] ; New York : Insight Media [distributor], 1999)
Overview of how exercisers can maximize the amount of fat that they burn. The video also offers specific strategies for increasing caloric expenditure during exercise
Title from title screen
Keywords: Weight loss; Metabolism